1987
DOI: 10.1016/s0004-9514(14)60579-1
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation in Human Flexibility and Grip Strength

Abstract: The main aim of this study was to monitor changes in joint flexibility over 24 hours in 25 subjects. Measurements of finger tip to floor, lumbar flexion, lumbar extension, passive straight leg raising and glenohumeral lateral rotation at 90° abduction were taken every two hours during the 24 hour cycle. The presence of circadian rhythms in flexibility were established by graphical analysis of the results. These were shown to exist in all measurements, the most strong being finger tip to floor and most weak gle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
6

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 23 publications
3
12
0
6
Order By: Relevance
“…The improved flexibility of the afternoon and evening groups as compared with the morning group is supported by the findings of Gifford [35], who showed that the fingertip to floor was stiff at 06:00 h, and the flexibility gradually increased to maximum at midday to midnight. Similarly, lumbar flexion measurements demonstrated the highest stiffness in the morning, with flexibility increasing to the peak in late afternoon and early evening, followed by increased stiffness.…”
Section: Discussionsupporting
confidence: 58%
“…The improved flexibility of the afternoon and evening groups as compared with the morning group is supported by the findings of Gifford [35], who showed that the fingertip to floor was stiff at 06:00 h, and the flexibility gradually increased to maximum at midday to midnight. Similarly, lumbar flexion measurements demonstrated the highest stiffness in the morning, with flexibility increasing to the peak in late afternoon and early evening, followed by increased stiffness.…”
Section: Discussionsupporting
confidence: 58%
“…While the timing of exercise varied from -5 to +4 hours around the body temperature minimum, exercise induced a one-to two-hour phase delay; and there was a tendency toward a smaller phase delay when exercise was performed in the latter part of the night and in the early morning. Buxton et al 63) reported a similar finding revealing a small phase Flexibility 29,36) Better in the evening than in the morning…”
Section: Effects Of Exercise On Human Circadian Rhythmsmentioning
confidence: 73%
“…These studies have demonstrated different circadian rhythmicities depending on the particular component. Fitness components, including short-term power output 27,28) , muscle strength 29,30) , and flexibility 29) , reach their peak and nadir at around evening and early morning, respectively. The difference between the peaks and nadirs in fitness indices is up to about 20%, except for flexibility, which shows a larger difference with its lowest value at midnight.…”
Section: A Variety Of Human Circadian Rhythms and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gün içindeki boy uzunluğunda meydana gelen kayıplarla ilgili deneysel çalışmalarda, farklı oranlarda boy kaybı ve geri kazanımı hem deneysel düzeneklerle hem de gözlemsel çalışmalarla gösterilebilmektedir. [18][19][20][21] Birçok çalışmada, kişilerin boy uzunluklarının gün içinde %1-1,7 arasında veya 20 mm'ye kadar etkilenebildiği gösterilmiştir. Boydaki bu değişik-likler birden fazla etkene bağlı olsa da en temel neden, gün içerisinde aksiyel iskelete binen yük olarak ifade edilmektedir.…”
Section: Gün İçi̇ Boy Uzunluğu Deği̇şi̇kli̇kleri̇ Ve Bu Deği̇şi̇kli̇kleri̇n Neunclassified